Political communication and cognition - Lilleker, Darren G.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Political Communication and Cognition draws on a range of theories from communication psychology to explain how citizens receive communication about politics, how communication might make a citizen think and importantly what stimulates political participation, whether simply paying attention, chatting online or going to vote.
Keywords: Science; Science, general